پێکهاته و ڕۆڵی پێشبهند له شێوەزاری ههورامیدا - حهمهئهمین, خۆشنـ او عهزیز; موحهممهد, شههرەزاد نایب; عهزیز, سالم حهسهن (Sulaimani Journal for Humanities, 2021)
The elements of language are varied according to their grammatical mode. Studying each component in a particular dialect and sub-dialect is invaluable consequently this subject is specified to study the form and function of preposition in Hawrami Sub-Dialect. Nevertheless only few limited resources are available about this subject and it has remained unstudied in detail similar to the other dialects. On the other hand, analyzing the prepositiones, their function and occurrence has an essential value because of their contribution in the morphological and syntactical structures and devouring function in the sentence. Moreover, in semantics level they convey several explicit connotations. Synchronic Descriptive Analysis Method has been utilized in this study. Besides to the preface which is an entrance to the subject, the accomplishment of the objectives of this research has required to divide the study to two unites. In the first unit, the theoretical part of the study, the types of preposition and their occurrence have been analyzed. In the first section, introduces the prepositiones and suffixes in Kurdish Language and the second section has devoted to study the categories and occurrence of preposition in Hawrami Sub-dialect. The second unit is the practical section in which the prepositiones’ role in Hawrami Sub-dialect has been studied through analysis and examples. At the end, the results, the bibliography and the summery of this study in Kurdish, Arabic and English languages have been included.
Keywords: Preposition; suffix; phrase; Morpheme; function; Grammatical; element